Status of Dispute Resolution of Village Head Decision Based on Commercial Administrative Decision Law - Hanin Alya Labibah; Arum Ayu Lestari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
In the scope of the smallest area, the village is led by a village head. Of course, the village head also has the authority to provide policies in the form of decisions on several things that occur within his coverage area. This type of research is normative legal research with a statutory approach and a conceptual approach. From this research, it can be concluded that the village head is not a state agency/official, even though the village is given authority by law that the village head as the village leader is given free authority. In the event that the village head's regulation that results in a decision is considered contrary to the public interest or contrary to other laws and regulations above it, then it can be canceled by the Regent / mayor instead of being carried out by the village head, so the village head's decision cannot be said to be KTUN.